Renal epithelial injury and fibrosis - Kaissling, Brigitte; Le Hir, Michel; Kriz, Wilhelm (Biochimica et biophysica acta. Molecular basis of disease, 2013)
Chronic kidney disease at a certain advanced stage inevitably progresses to end stage renal failure characterized by the progressing loss of nephrons accompanied by the increasing appearance of fibrotic tissue, called renal fibrosis. The urgent question is whether renal fibrosis is a response to injury or if fibrosis acquires a self-sustaining progressive potential that actively contributes to the deterioration of the kidney. The present review distinguishes between renal fibrosis subsequent to a glomerular injury and fibrosis subsequent to a primary tubular injury. Glomerular diseases enter a progressing course after encroaching onto the tubule leading to what is generally called “tubulointerstitial fibrosis”. The progression of the injury at the level of the tubulointerstitium appears to be fully dependent on the progression of the disease in the corresponding glomerulus. Primary tubular injuries have a very good chance of recovery. If they develop a local fibrotic process, this seems to be supportive for recovery. Cases in which recovery fails appear to secondarily initiate a glomerular disease accounting for a glomerulus-dependent vicious cycle to progression. Even if most researchers think of renal fibrosis as a process promoting the progression of the disease this review points out that the available structural evidence speaks in favour of a protective role of fibrosis supporting recovery after acute tubular injury or, under progressing circumstances, providing a firm three-dimensional framework that permits still intact or partially damaged nephrons to survive. This article is part of a Special Issue entitled: Fibrosis: Translation of basic research to human disease.